Inércia da taxa de juros : teoria e evidência para a economia brasileira (2005-2013) - Silva, Manuel Joaquim da Natividade (2014)
Regarding the monetary policy conduction, the reaction functions estimated in many empirical studies – for the Brazilian economy and other economies – have shown a good fit to data. However, these studies also report that the explanatory power for the estimates improves considerably when it includes a component of interest rate smoothing, represented by the lagged interest rate. According to Clarida, et. al. (1998) the lagged interest rate coefficient (between 0,0 and 1,0) represents the degree of monetary policy inertia, and when it becomes higher the response of interest rates to all relevant information becomes lower. The international literature has shown that such a component plays a significant role in the reaction function, which means that the central banks set interest rates slowly and parsimonious over time. However, the Brazilian case is particularly interesting, because more recent studies have shown an increase of the inertial component, suggesting that the BCB has increased the degree of interest rate smoothing in recent years. In this context, rather than to estimate a forward looking reaction function for the Brazilian Central Bank from January 2005 to May 2013, the current study aims to seek answers for a possible dynamic causality relationship between the trajectory of the inertia coefficient and relevant macroeconomic variables. For this purpose, we applied the Kalman Filter method to extract the trajectory of the inertia coefficient and then we estimated a Vector Autoregressive model (VAR) including the path of such an inertia and relevant macroeconomic variables. In general, the result for both Kalman filter method and the estimated reaction functions showed a high degree of inertia and a small overall coefficients response, what is inconsistent with the theory. The main finding from the VAR method was that positive shocks of the inertia variable were responsible for positive deviations on the output gap which in turn caused persistent inflation and inflation expectation deviations from the target.